L’accès aux institutions scolaires des communautés dont la langue est fragile : une perspective canadienne - Marie Mc Andrew (Brussels Studies)
After examining certain elements in the debate regarding the control of access to the educational institutions of communities whose language is in a fragile situation, the author presents the contrasting choices made in this respect over the past forty years by the French-speaking minority in Canada depending on whether or not it has the status of regional majority, as well as some of the consequences. The Canadian experience illustrates two approaches, namely that of the protection of a fragile minority by limiting access to the educational institutions it controls to people who have a historical or special connection to the language which defines it, or the dynamic use of schooling in an objective to transform ethnolinguistic relationships. Both approaches have some relevance. However, the first is clearly defensive and should be limited to groups whose vulnerability – which is not historical yet nevertheless present – is still recognised. The second has many more advantages and testifies to a dynamic definition of belonging and culture, which guarantees significant future development.